Artificial Intelligence and Its Reportage in Select Nigerian Newspapers: A Content Analysis - Guanah, Jammy; OBI, Ijeoma; GINIKACHUKWU, Alpha Chukwuemeka (International Journal of Language and Literary Studies, 2020)
The emergence of Artificial Intelligence (AI) is gradually having effects in most facets of the society; and no area tends to be exempted from this AI bug. This research explored the discourses of the place of the media, especially newspapers, as the watchdogs of the society in this unfolding scenario. It was expected that the media should be at the forefront in letting citizens know its implications. The study set out to determine the volume of coverage given to news about Artificial Intelligence (AI) by The Punch, The Guardian, and Vanguard newspapers; to identify the story types through which AI stories were reported by the newspapers, and to examine if the newspapers gave prominence to AI stories. The study was anchored on the Agenda Setting Theory while Content Analysis was adopted as the research method for obtaining data from a population of 1,095 made up of the newspapers` editions from January to December 2019, and a sample size of 285 derived through the use of the Creative Research System Calculator. The study revealed that only 64 AI stories appeared in the selected newspapers throughout 2019. It also discovered that most of the stories were in photograph form, and that prominence was not given to AI stories by the newspapers. It was therefore concluded that since automation may be the future, newspapers must start to intensify in educating the public about AI through their coverage. The study recommended among other things that newspapers should give prominence to AI stories. Also, they should report AI stories with all story types, and place such stories in all the prime sections of the newspapers.